DESIGNING A PERFORMANCE APPRAISAL SYSTEM FOR MANAGEMENT CONSULTANT OFFICE “D” - Susanto, Susanto; Darmasetiawan, Noviaty Kresna (Dinasti Publisher, 2020)
This design aims to conduct a job analysis and designing a performance appraisal system for Management Consultant Office